Kolaborasi Orang Tua Dan Guru Dalam Menanamkan Nilai Akidah Dan Akhlak Pada Siswa Di SD IT Al Habib Serdang Bedagai - Nursella Majid; Nikmah Royani Harahap; Ade Rahman Matondang (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2026)
This study aims to describe the forms of collaboration, applied strategies, and the supporting and inhibiting factors in the collaboration process between parents and teachers in instilling the values of faith (akidah) and morals (akhlak) in students at SD IT Al Habib Serdang Bedagai. This research uses a qualitative approach with a case study method. Data were collected through observation, in-depth interviews, and documentation. The results show that collaboration between parents and teachers is established through regular communication, parental involvement in religious activities, and the alignment of values between home and school environments. The strategies implemented include modeling, habitual practices, and reinforcement through advice and emotional approaches. Supporting factors include shared Islamic values, school program support, and parental awareness, while inhibiting factors consist of time constraints, differing family backgrounds, and limited two-way communication. The findings indicate that the successful inculcation of akidah and akhlak in students is highly dependent on the quality of collaboration between school and family. Therefore, strengthening synergy and intensive communication between teachers and parents is crucial in shaping students' Islamic character comprehensively.